Assessment of genotype x environment interaction and stability of sesame (Sesamum indicum L.) seed yield under rainfed and supplementary irrigation in central Sudan - Eltayeb, Badr Eldin K.; Ali, Khalafalla A (Gezira Journal of Agricultural Science, 2014)
ABSTRACT       Sesame knowledge of genotype x environment interaction (GEI) is advantageous in order to have a cultivar that gives consistently high yield in a broad range of environments and to increase the efficiency of breeding programs and selection of the best genotypes. Fifteen genotypes of sesame ( Sesamum  indicum L.) were evaluated during 2011 and 2012 rainy seasons, at Wad Medani, Rahad (under supplementary irrigation) and Gedarif (under rainfed), to assess genotype x environment interaction and stability of seed yield. A randomized complete block design with four replicates was used in each location. The analysis of variance procedure revealed highly significant differences among the 15 sesame genotypes for seed yield over the eight environments. The mean squares of environment, genotype and genotype x environment interaction were highly significant for seed yield. Both statistical stability models, i. e. Eberhart and Russell (1966) as well as the Additive Main Effect and Multiplicative Interaction (AMMI) analysis, indicated that genotypes Elgezouli, Promo, Um Shagra and Kenana-2 were the most high yielding and stable genotypes and can be recommended for both rainfed and irrigated areas of central Sudan.                من ميزات دراسة التفاعل الوراثي- البيئي في محصول السمسم معرفة افضل الاصناف ذات الانتاجية العالية في مدي واسع من البيئات المختلفة مما يزيد من كفاءة برامج التربية المستعملة وانتخاب افضل الاصناف. تم تقويم 15 سلالة من السمسم في الموسمين الزراعيين 2011 و2012م في ثلاثة مواقع هي مدني، الرهد (ري تكميلي) والقضارف (ري مطري)، وذلك لتقويم التفاعل الوراثي والبيئي وثبات درجة انتاجية بذور السمسم. استخدم تصميم القطاعات العشوائية الكاملة بأربع مكررات. اظهرت نتائج تحليل التباين لعدد 15 سلالة من السمسم فروقات معنوية عالية جدا لمعظم الصفات التي درست في كل المواقع والمواسم مع معنوية للتفاعل الوراثي والبيئي لإنتاجية البذور. بناءاً علي نماذج التحليل Eberhart and Russel (1966)              وAdditive Main Effect and Multiplicative Interaction(AMMI) لتحديد ثبات الاداء معاً وجد ان انتاجية بذور الاصناف الجزولي، برومو، ام شجرة وكنانة-2 ثابتة وعالية في كل المواقع والمواسم. وبناءاً علي ذلك يوصي بزراعة هذه الاصناف في المناطق المطرية والمروية في وسط السودان.